Aplikace fuzzy logiky pro určení priority testů - Starostová, Andrea (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce je zaměřena na stanovení priority testovacích případů s využitím fuzzy logiky. Vhodným přístupem k získání výstupu na základě definovaného vstupu a stanovených pravidel byl zvolen fuzzy model přiřazující prioritu testovacím případům. K dosažení cíle práce byla nejprve stanovena kritéria, parametry a poté určena jejich váha pro jednotlivé testovací případy. Na závěr jsou vyhodnocena vstupní data s využitím řešení v programu MS Excel a MATLAB.

The master’s thesis focuses on determination of Test case priority using Fuzzy logic. As principle of Fuzzy logic is a convenient way to turn given inputs to final output according to defined rules, a Fuzzy based model for assigning Test case priority has been chosen. In order to fulfil the aim of the thesis, firstly particular criteria along with parameters set to each Test case and its weights needs to be defined accordingly. So as to come to the conclusion and evaluate input data, the solution for computing in the program MS Excel and MATLAB is used herein.
The Application of Fuzzy Logic for Test Case Prioritization
Keywords: Fuzzy logika; Fuzzy Logic Toolbox; Vývoj softwaru; Testování softwaru; Testovací případ; Fuzzy Logic; Fuzzy Logic Toolbox; Software development; Software testing; Test cases